T.S. Eliot's orchestra: Critical essays on poetry and music - Cooper, John Xirox (New York Garland Publishing, 2000)
Nearly everyone who addresses Eliot's imaginative and critical work must acknowledge the importance of music in thematic and formal terms. This collection of original essays thoroughly explores this aspect of his work from a number of perspectives.